ТЕОРЕТИЧНІ ТА ПРАКТИЧНІ АСПЕКТИ ВИЗНАЧЕННЯ КРЕДИТНОГО РЕЙТИНГУ БАНКІВ В УКРАЇНІ - Ганзюк, Світлана Михайлівна; Каграманян, Ельміра Арсенівна (Науковий журнал «Світ фінансів», 2018)
Ганзюк С. М., Каграманян Е. А. Теоретичні та практичні аспекти визначення кредитного рейтингу банків в Україні. Досліджено економічну сутність кредитного рейтингу банків. Систематизовано теоретичні положення щодо визначення рейтингу за різними ознаками відповідно до їх змісту. Уточнено сутність дефініції “рейтинг банку”. Визначено основні уповноважені міжнародні та національні рейтингові агентства. Досліджено вітчизняні базові підходи до присвоєння кредитних рейтингів банкам. Проаналізовано кредитний рейтинг українських банків. Ганзюк С. М., Каграманян Э. А. Теоретические и практические аспекты определения кредитного рейтинга банков в Украине. Исследована экономическая сущность кредитного рейтинга банков. Систематизированы теоретические положения по определению рейтинга по разным признакам в соответствии с их смыслом. Уточнена сущность дефиниции “рейтинг банка”. Определены основные уполномоченные международные и национальные рейтинговые агентства. Исследованы отечественные базовые подходы к присвоению кредитных рейтингов банкам. Проанализирован кредитный рейтинг украинских банков. Ganziuk S., Kahramanian E. Theoretical and practical aspects of determining the credit rating of banks in Ukraine. Introduction. The developed financial market implies the existence of a common system of classification of financial institutions by categories of reliability. Ratingscore allows the client to identify the bank in which it is safe to invest, and partners of the banking institutions inside the interbank market. Accordingly, issues of clarification of the essence of the Bank’s credit rating, the study of the theoretical peculiarities of its definition and practical aspects of its application in Ukraine become of particular urgency and importance. Purpose. The purpose of the article is to study the essence of the rating and credit rating of the bank and the analysis of the state of development of the national rating assessment of banks activity in Ukraine. Results. The economic essence of the credit rating of banks is investigated. The theoretical positions on rating according to different characteristics according to their content (assessment, characteristic, system, indicator, method, installation, process, distribution, tool, forecast) are systematized. The essence of the definition of “bank rating” is specified. The main authorized national rating agencies are identified. The domestic basic approaches to assigning credit ratings to banks are investigated. The credit rating of domestic banks of Ukraine is analyzed. Conclusions. Credit rating is the main source of information for clients and investors, on the basis of which the choice of the bank is made for investing clients’ funds and formulating strategic goals and tasks of development of the banks themselves. There are various methodological approaches to determining the essence of the bank’s credit rating, its analysis and evaluation. Modern rating assessments should be adapted for Ukrainian banks and correspond to the real financial situation of a banking institution. Prospects for further research are the development of alternative methods of assessing the activities of banks, which would have been noticed, first of all, by the simplicity of calculations, and the results of which would be available to a wide range of consumers.